Study of the intrinsic properties of wheat bran and pearlings obtained by sequential debranning and their role in bran-enriched bread making. (September 2016) - Hemdane, S.; Langenaeken, N.A.; Jacobs, P.J.; Verspreet, J.; Delcour, J.A.; Courtin, C.M.
Abstract: To gain insight in the causes of bread volume and crumb texture quality loss upon incorporation of wheat bran, the hydration properties, overall reducing compound levels and bran-associated enzyme activities of ground bran and bran pearling fractions were studied and related to their impact on bread making. Sequential pearling of wheat kernels to 3, 6, 9 and 12% by weight yielded pearling fractions P0–3%, P3–6%, P6–9% and P9–12%, strongly differing in hydration and (bio)chemical properties. Pericarp-rich fraction P0–3%, having the highest water binding and water retention capacity, showed the most adverse effects on bread volume and crumb texture, whereas addition of aleurone-rich fraction P6–9%, having low water binding and water retention capacities, showed less adverse effects on bread properties. P3–6% and P9–12% addition showed intermediate results, with a bread volume comparable to the control bread containing ground bran sample. Comparison of the effect of a heat treated versus a native fraction P0–3%, having a high bran-associated enzymatic activity, showed that bran-associated enzymes can clearly affect the Hagberg Falling Number of meal and bread crumb textural properties, but not bread volume. Overall, results suggest that bran hydration properties and enzymatic load affect the bread making potential. Highlights: Pearling yields bran fractions differing in biochemical and hydration properties. Pericarp-rich fractions are more deleterious to bread volume and crumb texture. Aleurone-rich fraction P6–9% affects bread making less than control ground bran. Mainly bran hydration properties are believed to impact bread volume. Bran-associated enzymes can affect Hagberg Falling number and bread crumb texture.